2021
DOI: 10.1155/2021/7801365
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Smart Medical System Based on NB-IoT Technology

Abstract: In recent years, with the constant development and integration of Internet technology, Internet of Things technology, and intelligent terminal technology, to make people’s work and life more comfortable and convenient, these new technologies have been more and more widely used in daily home life such as social education, agricultural production, industrial production, medical, and other fields. However, at present, there are still a lot of room for development in the application of new technologies in the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Block query requires two steps. e first step is to construct a Bloom filter about all query indexes in each block, which is used to query whether there are spatial location attribute related data in the block; Part 2: Establish a double-layer combined Bloom filter of all query indexes in each block, which is used to query the exact location of the query index corresponding to the spatial location attribute [12]. Both query structures use hash function to construct encrypted query index, which can quickly query data during query operation.…”
Section: Blockchain and Internet Of Things Technologymentioning
confidence: 99%
“…Block query requires two steps. e first step is to construct a Bloom filter about all query indexes in each block, which is used to query whether there are spatial location attribute related data in the block; Part 2: Establish a double-layer combined Bloom filter of all query indexes in each block, which is used to query the exact location of the query index corresponding to the spatial location attribute [12]. Both query structures use hash function to construct encrypted query index, which can quickly query data during query operation.…”
Section: Blockchain and Internet Of Things Technologymentioning
confidence: 99%
“…According to their analysis, a licensed frequency supported cellular network (e.g., NB-IoT) ensures reliable and efficient communication in the healthcare system. An intelligent medical plan was based on NB-IoT technology and a smart hospital information management system was developed and explored in [ 4 ].…”
Section: Related Workmentioning
confidence: 99%
“…Healthcare is boosted as an application domain that appears to be very promising for enhancing service quality of the patients due to the Internet of Things (IoT), cloud computing, and Wireless Body Area Network (WBAN) technologies, as well as the interactions among those [ 2 ]. Some wireless technologies (e.g., ZigBee, Bluetooth, LoRa, Sigfox) are used in healthcare applications; however, some recent studies [ 3 , 4 ] have already revealed that the Narrow Band IoT (NB-IoT) is more suitable for healthcare applications in terms of licensing policy, long-range data transmission performance, energy-efficiency, etc., than other technologies. The fact that the NB-IoT is a Low Power Wide Area Network (LPWAN) technology facilitating a long-range and deep indoor coverage makes it perfect for a typical smart hospital context [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al developed an intelligent hospital information management system based on internet technology to meet the functions of patient reservation, viewing medical records and hospital news. At the same time, it can also manage the hospital more comprehensively [14]. Onasanya and Elshakankiri used Internet of things technology to build an intelligent health care system for cancer care, increase the choice of existing treatment, and provide more solutions for health care [15].…”
Section: Related Workmentioning
confidence: 99%